Aetiology of paediatric facial trauma at a UK District General Hospital. (9th December 2014) - Lello, S.; Allen, P.; Haig, S.
Abstract Aim This study aims to determine the types and causes of facial injury in children who present to a UK District General Hospital (DGH), to evaluate the relevant demographics of the subjects and to investigate whether the events were accurately clinically coded. Materials and methods A retrospective review of all patients aged <1–17 years attending the emergency department (ED) in a DGH over the course of 1 month with a facial injury. Results Eighty‐four paediatric patients attended the ED with facial injuries during the month of September 2012. The male:female ratio was 2.36:1. Most injuries were due to a fall (49%). Six alleged assaults were recorded, but no other non‐accidental injury was suspected. Lacerations were the most frequent injury seen (44%). Dental trauma accounted for 9% of injuries. Sixty‐eight per cent of the subjects lived within the eight areas of Swindon that are among the most deprived 20% nationally. Eighteen per cent lived within the Penhill ward (electoral district), which has two areas among the most deprived 5% nationally. Ten per cent were referred on to specialist services within the hospital. Three children were referred to Oral and Maxillofacial Surgery. Only 25% of the visits to the ED were coded with sufficient detail. Conclusions The aetiology of facial trauma in children should be accurately recorded to allow the planning of accident prevention campaigns that can be targeted at a local and national level. This relies partly on the coding information collected from EDs and so it is imperative that this is detailed and accurate.